Expression profile of the amino acid transporters SLC7A5, SLC7A7, SLC7A8 and the enzyme TDO2 in basal cell carcinoma. (1st January 2019) - Tina, E.; Prosén, S.; Lennholm, S.; Gasparyan, G; Lindberg, M.; Göthlin Eremo, A.
Summary: Background: The incidence of basal cell carcinoma (BCC) is increasing and the costs for care rising. Therefore, the need for simplified and cost‐effective treatment choices is substantial. Aberrant signalling in several pathways, induced by ultraviolet radiation, is of importance in the development of BCC. Alterations in tumour metabolic activity are part of general carcinogenesis; however, these alterations are only partially recognized in skin cancer. Objectives: To study expression profiles in BCCs compared with individually matched nontumour skin, with a focus on finding differences associated with tumour metabolism. Materials and methods: Gene expression in biopsies from BCCs ( n = 14) compared with biopsies from nontumour gluteal skin was analysed with microarrays ( n = 4 + 4) and/or quantitative real‐time polymerase chain reaction (qPCR, n = 14 + 14). Protein expression and localization was assessed using immunohistochemistry (IHC) in formalin‐fixed and paraffin‐embedded BCC samples. Results: Microarray analysis revealed increased expression of the amino acid transporters SLC7A5, SLC7A7 and SLC7A8 as well as the cytosolic enzyme tryptophan 2, 3‐dioxygenase (TDO) 2 in BCC. Higher expression of SLC7A5 ( P < 0·001), SLC7A8 ( P < 0·001) and TDO2 ( P = 0·002), but not SLC7A7 ( P = 0·50), was confirmed by qPCR, and IHC demonstrated correlating tumour cell protein expression of SLC7A5 and SLC7A8. Protein expression of SLC7A7 was observed in the stratum granulosum, and TDO2 in immune cells. Conclusions: This study highlights the upregulation of SLC7A5, SLC7A8 and TDO2 in BCC compared with nontumour skin. Our findings imply that amino acid transporters may be further explored as potential targets for future medical treatment.